Performing the Possibilities of First-Year Teaching - Vanover, Charles (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2025)
In this article I describe the development of an ethnodrama intended to investigate relationships between 1st-year teachers and students of colour. Excerpts from the script, photographs of performers, and artists’ interviews communicate the sensations of life in school. The show evokes the power of the classroom to hurt and to heal. It is intended to help the audience imagine the power of strong classroom relationships and the damage of negative connections. These efforts seek to deepen understandings of the ambiguous nature of beginning teachers’ work and provide a guide for future investigations of schools and classrooms. In the conclusion, I share implications of the performance for educational policy and Research-based Theatre (RbT).